Perjanjian Kredit Bank dengan Jaminan Borgtocht (Perorangan) - I Gusti Ngurah Bagus Denny Hariwijaya; I Nyoman Putu Budiartha; I Ketut Widia (Jurnal Konstruksi Hukum, 2020)
The rapid progress of the times is influenced by the development of the needs of every member of society and the ways of fulfilling the economy of each member of society. This incident requires the presence of a credit guarantee regulation as a place to expand a business that has both a legal entity and an individual. Granting space for credit requires a guarantee for the sake of security. Lending requires a guarantee such as a house, land, car, shares, and other assets for the sake of security for the credit extension and to avoid risks if a debtor cannot fulfill his obligations. From this certainty, it is possible for the Bank to provide credit with individual guarantees, but the Bank should have confidence in the ability and intelligence of the debtor to repay his debt. Based on this background, this research was conducted with the aim of describing the legal consequences arising from a credit agreement involving a third party as a guarantor. This study was designed using a normative juridical approach. The results of this study indicated that the legal consequences arising from a credit agreement involving a third party as a guarantor, namely: first, a debtor can be sued by an insurer who has paid the creditor's debt. The coverage can occur with the knowledge or without the knowledge of the debtor himself. Second, the insurer has the right to demand compensation and interest. Third, creditors and insurers must pay attention to certain rights and obligations. Finally, the insurer or third party is given the right to share the debt, that is, when sued for the fulfillment, can claim shares from their party as the guarantor.